2007
DOI: 10.1253/circj.71.1387
|View full text |Cite
|
Sign up to set email alerts
|

Early and Mid-Term Impacts of Cardiopulmonary Bypass on Coronary Artery Bypass Grafting in Patients With Poor Left Ventricular Dysfunction A Propensity Score Analysis

Abstract: ff-pump coronary artery bypass grafting (OPCAB) is an alternative to conventional cardiopulmonary bypass-supported myocardial revascularization and is becoming increasingly popular, as it allows complete myocardial revascularization with excellent surgical results in most patients. 1,2 Severe left ventricular dysfunction has been reported to be an independent predictor of operative mortality in patients undergoing coronary artery bypass grafting (CABG) and patients with impaired left ventricular function und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 28 publications
2
27
0
Order By: Relevance
“…Death from non-cardiac causes was similar between the two groups (15.5%, n = 21) in the low LVEF group, compared with 10.2% (n = 112) in the normal LVEF group ( p = 0.13). Youn et al showed similar midterm results in patients with depressed LV function as OPCAB revascularization resulted in a survival rate of over 80% at 6 years [23]. Suzuki et al recently reported comparable midterm results, as the 5-year freedom from death from all causes was 57% in an OPCAB group of patients with a low LVEF.…”
Section: Discussionmentioning
confidence: 86%
“…Death from non-cardiac causes was similar between the two groups (15.5%, n = 21) in the low LVEF group, compared with 10.2% (n = 112) in the normal LVEF group ( p = 0.13). Youn et al showed similar midterm results in patients with depressed LV function as OPCAB revascularization resulted in a survival rate of over 80% at 6 years [23]. Suzuki et al recently reported comparable midterm results, as the 5-year freedom from death from all causes was 57% in an OPCAB group of patients with a low LVEF.…”
Section: Discussionmentioning
confidence: 86%
“…Youn et al [30] also showed similar 6-year survival rates (88% in OPCAB versus 72% in ONCAB) and freedom from major adverse cardiovascular events.…”
Section: Left Ventricular Dysfunctionmentioning
confidence: 77%
“…Two recent comparisons of OPCAB and ONCAB in patients with LV dysfunction (defined as ejection fraction <35%) revealed a reduction in perioperative morbidity in OPCAB patients, specifically with respect to ICU LOS, respiratory failure, need for intotropes, and need for intraaortic balloon counterpulsation (IABP) [29,30]. Youn et al [30] also showed similar 6-year survival rates (88% in OPCAB versus 72% in ONCAB) and freedom from major adverse cardiovascular events.…”
Section: Left Ventricular Dysfunctionmentioning
confidence: 97%
“…65 In addition, the long-term results were improved by CABG with arterial grafts and complete revascularization in Asian countries as experienced in Western countries. 66,67 Hence, we need future research into whether widespread DES use will improve outcomes and save costs in the treatment of various subsets of coronary artery disease.…”
Section: Special Issues In Asiamentioning
confidence: 99%